1991
DOI: 10.1101/gad.5.9.1538
|View full text |Cite
|
Sign up to set email alerts
|

Regulated expression of three C/EBP isoforms during adipose conversion of 3T3-L1 cells.

Abstract: In an effort to identify protein factors that play a regulatory role in the differentiation of adipocytes, we have isolated two genes that encode polypeptides related to CCAAT/enhancer-binding protein (C/EBP; hereafter termed C/EBP alpha). The proteins encoded by these C/EBP-related genes, termed C/EBP beta and C/EBP delta, exhibit similar DNA-binding specificities and affinities compared with C/EBP alpha. Furthermore, C/EBP beta and C/EBP delta readily form heterodimers with one another as well as with C/EBP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
1,324
2
13

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,559 publications
(1,383 citation statements)
references
References 71 publications
44
1,324
2
13
Order By: Relevance
“…(4) Ectopic expression of C/ EBPalpha counteracts the FMIP-induced differentiation phenotype and siRNA inhibition of C/EBPalpha partially mimics the effect of FMIP. It has been clearly demonstrated that C/EBPalpha is a key player in adipocyte differentiation (Cao et al, 1991;Lin and Lane, 1994;Hu et al, 1995). For example, fibroblasts differentiated into adipocytes following ectopic expression of C/EBPalpha (Freytag et al, 1994;Park et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) Ectopic expression of C/ EBPalpha counteracts the FMIP-induced differentiation phenotype and siRNA inhibition of C/EBPalpha partially mimics the effect of FMIP. It has been clearly demonstrated that C/EBPalpha is a key player in adipocyte differentiation (Cao et al, 1991;Lin and Lane, 1994;Hu et al, 1995). For example, fibroblasts differentiated into adipocytes following ectopic expression of C/EBPalpha (Freytag et al, 1994;Park et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…As FMIP influences myeloid differentiation as well, we examined the common key factors in both differentiation systems. One candidate is a protein belonging to the C/EBP family (Cao et al, 1991;Wang et al, 1995;Tenen et al, 1997;Lane et al, 1999), as it has been demonstrated that timely expression of C/ EBPalpha and C/EBPbeta is essential for adipocyte differentiation (Fux et al, 2004;Mori et al, 2005). Therefore, we examined the expression of C/EBPalpha and C/EBPbeta during differentiation in FMIP-overexpressing and knockdown cells.…”
Section: Fmip Influences the Expression Of C/ebpalpha Gene During Adimentioning
confidence: 99%
“…Expression of antisense C/EBPα RNA prevents both growth arrest and terminal differentiation of 3T3-L1 adipocytes [18]. In addition, C/EBPα is critical in regulating the differentiation of preadipocytes, myeloid cells, hepatocytes and pneumocytes [3,5,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In cells with more modest levels of C/EBPα or none at all, C/EBPβ, if it receives the appropriate post-translational signals or is increased to sufficiently high levels, activates the 11β-HSD1 P2 promoter. A549 cells contain very low levels of C/EBPα, as do 3T3-L1 preadipocytes (Cao et al, 1991;Li et al, 1995;Sai et al, 2008). C/EBPα, essential for myeloid cell differentiation (Zhang et al, 1997) and a neonatal inflammatory response (Burgess-Beusse and Darlington, 1998) has been shown to decrease the transactivation potential of C/EBPβ through control of isoforms expressed (Burgess-Beusse et al, 1999) and thus may suppress transactivation by C/EBPβ in liver under normal circumstances.…”
Section: The Transcriptional Regulation Of 11β-hsd1mentioning
confidence: 99%